GERAK IRAMA SALAH SATU ALTERNATIF UNTUK MENGENALKAN KONSEP RUANG BAGI ANAK KESULITAN BELAJAR - Eci Fitriwati, Irdamurni, Markis Yunus (Universitas Negeri Padang, 2013)
background of this research by the issues raised in SDN 18 Koto Luar Kec. Pauh Padang difficulties that children learn x 8-year-old second grade who have difficulty in recognizing the concept of space particularly the right and left. This study aims to improve the ability to know the concept of space for children to learn through movement difficulties rhythm. Methodology of this study, single subject research (SSR) with ABA research design is a design that compared the ability of space for children to know the concept of learning difficulties in consistent Shanghainese x baseline, intervention by using the motion without using a baseline rhythm and cadence of motion. Assessment conducted in this study is consistent in measuring the large number of correct answers of the concept of space (right and left) are shown, mentioned and exhibited learning difficulties children are presented in the form of a percentage. From the results of the study can be seen in the baseline condition 1 (A1) conducted in eight meetings, the meetings of one to eight children only able to get a score of 0%. Children are not able to show, mentions and demonstrate the concept of space (right and left) correctly. After being given treatment in the intervention condition children's ability to carry out the introduction of the concept of space (right and left) increases. Data showing the stability of nine to seventeen meetings with the highest score of 100% with the results of children were able to answer all questions correctly. Then in the baseline condition 2 (A2) with no treatment is given, the data demonstrate the stability of the meeting to eighteen to twenty-one with the highest score of 100% with the results of children were able to answer all questions correctly.